Medinilla saxa (Melastomataceae: Sonerileae), a new, ultramafic rock-dwelling species from the Philippines - Fernando, Edwino S.; Quimado, Marilyn O.; Quakenbush, J. Peter (Phytotaxa, 2025)
A new species, Medinilla saxa Fernando, from ultramafic rocks on Luzon Island, Philippines is described and illustrated. The species is most similar to Medinilla whitfordii Merr. in its 3-plinerved leaves and inflorescence of terminal, erect cyme. It differs, however, in its low shrub growth habit of 10–30 cm tall (vs erect shrub or tree 3–5 m tall) and 4-merous flowers (vs 5–6-merous flowers). It is also compared with other similar species in the Medinilla whitfordii group with terminal cymose inflorescence.